A comparison of sight and touch features of image formation - Lapė, J. (Psichologija, 1964)
Experimentally obtained data confirms the idea that the visual and tactile analyzers have something in common. The data presented indicates that the analyzers reflex dynamics workflow changes causes changes in an emerging image. If visual and tactile analyzer reflex dynamics workflow changes are similar, then  visual changes the resulting in both modes of perception are of a similar nature. That supports the argument that three-dimensional image formation takes place in a similar manner on the basis of visual and tactile analyzer activity.
Keywords: touch; vision; perception; image formation